Quantifying the value of a clean ride: How far would you bicycle to avoid exposure to traffic-related air pollution?. (November 2017) - Anowar, Sabreena; Eluru, Naveen; Hatzopoulou, Marianne
Highlights: SP Survey to evaluate the impact of air pollution on bike route choice is conducted. Air pollution exposure externalities considered: mean and maximum exposure. Data from 695 commuter cyclists was analyzed using a random utility approach. Value of Clean Ride for mean and maximum exposure: 0.72 and 0.25 min/ppb. Cyclists exhibit intentions to change route to avoid air pollution exposure. Abstract: While there is widespread acceptance of the health benefits of bicycling, recent research has highlighted that the benefits may be partially offset by the potential adverse health impacts as a result of bicyclists' exposure to traffic-related air pollution. Using a stated preference experiment, data from 695 commuter cyclists was compiled through a web-based survey and analyzed using a random utility approach to evaluate whether and to what extent cyclists are willing to trade-off air pollution exposure with other attributes such as roadway characteristics, bike facilities, and travel time. Mean and maximum concentrations of nitrogen dioxide (in parts per billion or ppb), a common marker of traffic-related air pollution, were used as the attributes to represent the externality (ranging from 5 to 60 ppb). Empirical results indicate that travel time and traffic volume remain the most important attributes for commuter cyclists in their route decision. We also computed a unique marginal rate of substitution called "Value of Clean Ride" (VCR). For mean exposure, the VCR is: 0.72 min/ppb and for maximum exposure, the VCR is: 0.25 min/ppb (95% distribution: −0.16, 0.67). This essentially suggests that if an alternative route was available with an average nitrogen dioxide concentration that is lower by 5 ppb (a realistic goal in light of the high spatial variability in air pollution within urban areas), then cyclists would be willing to take it if it added no more than about 4 min to their travel time. We also observed that cyclists who received information on short-term impacts of traffic-related air pollution tended to be more concerned with avoiding maximum exposure.